Perkembangan Pembangkit Listrik Tenaga Hibrida (PLT Hibrida) Di Indonesia Guna Mendukung Ketahanan Nasional - Syam, Dzilal Iksan; Thamrin, Suyono; Maharani B.Z , Cahya (PendIPA Journal of Science Education, 2024)
Hybrid Power Plant is one of the alternatives to meet electricity demand in Indonesia and has experienced significant development in recent years. Hybrid power plants are a solution in increasing the electrification ratio by meeting electricity needs in remote areas and being a solution for new renewable energy that is intermittent A hybrid Power Plant must achieve optimal function so that a strategy is needed to increase optimal achievement. This research aimed to analyse the development of hybrid power plants in Indonesia and identify factors that can optimise the development of hybrid power plants in Indonesia. This research was qualitative and used a literature study method. SWOT analysis became an analytical tool to identify internal and external factors. The results of this study show that hybrid power plants support energy security and national security. Hybrid power plants' strengths (S) are that they can increase reliability, are environmentally friendly and synergise with energy transition. Weaknesses (W) are that some hybrid power plants still utilise fuel for integration and the technology is more complicated. Opportunities (O) are that hybrid power plants can reduce the achievement of electrification ratio, NZE and energy transition. Threats (T) are financing and geography.